2000
DOI: 10.1007/s003300000362
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery blood flow: quantification with breath-hold or respiratory triggered phase-contrast MR imaging

Abstract: The aim of this study was to evaluate the validity and reproducibility of breath-hold and respiratory triggered phase-contrast (PC) MR imaging techniques in the measurement of renal artery blood flow. In 12 healthy subjects cardiac-gated PC flow measurements were obtained in the renal arteries using a breath-hold and a respiratory-triggered technique. The flow measurements were repeated in each renal artery separately. Comparison between the sum of flow measurements in the renal arteries and the difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Because these substances rely on almost total clearance from the blood by filtration and tubular excretion to determine blood flow, they are inaccurate in the setting of severe glomerular and tubular dysfunction, shown by the large discrepancy with Doppler flowmeter or phase-contrast cinemagnetic resonance imaging blood flow values. [193][194][195] Thus, studies of RBF in the setting of ARF need to be repeated using methods independent of tubular influence. One such study of renal transplants found a decrease in renal plasma flow postoperative day 7 in patients with sustained renal failure compared with those with recovery.…”
Section: Recovery From Arfmentioning
confidence: 99%
“…Because these substances rely on almost total clearance from the blood by filtration and tubular excretion to determine blood flow, they are inaccurate in the setting of severe glomerular and tubular dysfunction, shown by the large discrepancy with Doppler flowmeter or phase-contrast cinemagnetic resonance imaging blood flow values. [193][194][195] Thus, studies of RBF in the setting of ARF need to be repeated using methods independent of tubular influence. One such study of renal transplants found a decrease in renal plasma flow postoperative day 7 in patients with sustained renal failure compared with those with recovery.…”
Section: Recovery From Arfmentioning
confidence: 99%
“…However, in a previously published study we have shown that quantitative measurement of renal artery blood flow with 2D PC MR is highly reproducible. 12 Still, the spread of MR results in the current study calls for further improvements before widespread clinical application of this technique can be advocated.…”
Section: Discussionmentioning
confidence: 93%
“…The accuracy of this technique was verified both in vivo and in vitro by comparison with other noninvasive (eg, duplex ultrasound and/or nuclear clearance techniques) and invasive techniques (implantation of ultrasound probes) or by internal validation by comparing aortic flow measurements above the renal arteries with the total flow through the renal arteries and aorta distal of these arteries. [12][13][14] In the current study, the 133 Xenon washout technique was used as an independent test for comparative evaluation of the acquired 2D PC MR renal artery flow data in hypertensive patients. The 133 Xenon washout technique requires selective arterial catheterization to allow local disposition of the tracer and therefore has the potential to provide information about blood flow of each kidney separately.…”
mentioning
confidence: 99%
“…Renal blood fl ow measurements by cine phase-contrast MRI are well correlated with simultaneous PAH clearance measurement [50] and the results are reproducible [51]. King et al [52] used this met hod as a tool to predic t clinical re sponse afte r percutaneous angioplasty in re nal artery stenosis.…”
Section: Cine Phase-contrast Mrimentioning
confidence: 99%